Inter-industry creative collaborations incorporating luxury fashion brands. Issue 3 (11th July 2016) - Alexander, Bethan; Contreras, Luis Ortega
Abstract : Purpose: – The purpose of this paper is to conceive the concept of inter-industry creative collaboration; a unique kind of cooperation between business partners from diverse industries. It investigates the motivations that encourage their creation and identifies a method to evaluate consumers' attitudes towards this kind of partnership. The study analyses consumer-based brand equity and links them to inter-industry creative collaborations within the luxury fashion industry. Design/methodology/approach: – Research was conducted using a comparative case design, which was qualitative in nature. Four cases were selected purposively. The data were obtained using semi-structured interviews with industry informants and consumer focus groups. Transcripts were thematically analysed according to common categories identified in the literature to enable cross-case conclusions to be drawn. Findings: – The research proposes the existence of a direct relationship between the consumer-based brand equity effects and consumers' attitudes towards inter-industry creative collaborations. This research not only proves the existence of the stated relationship but also generates a theoretical framework that specifically analyses inter-industry creative collaboration involving luxury fashion brands. Research limitations/implications: – The usage of convenience sampling limited consumer participants to individuals who considered themselves luxury fashion consumers. In addition, the findings are limited to London, UK and cannot be generalised outside the examined cases. That said, the research provides a useful starting point for further empirical research to test the validity and reliability of the model outside of the stated cases. Practical implications: – The proposed theoretical framework serves as a practical guide for luxury managers to assess the planning and execution of inter-industry creative collaborations conducted by their brands. Originality/value: – The research makes a contribution to brand management literature by creating a connection between four topics of academic research: motivations of inter-industry creative collaborations; consumer-based brand equity; consumers' attitudes towards inter-industry creative collaborations; and the creative and emotional elements of luxury fashion.